CHANGE OF NUTRIENT AND BIOACTIVE COMPONENTS IN BOVINE COLOSTRUM AFTER SPRAY DRYING - Thi Hoa Vien, Do; Quang Hoa, Le (Vietnam Journal of Science and Technology, 2017)
Bovine colostrum powder (BCP) was obtained by using spray drying method with the inlet temperature at 120oC and the outlet temperature at 60oC. Nutrient and bioactive components such as protein, lipid, lactose, mineral, glycoprotein (e.g. lactoferrin) and the immunoglobulins IgG, IgA and IgM in BCP were analyzed before and after spray drying process. Experimental results showed that the average values for total protein, lipid, lactose, mineral, lactoferrin in BCP were 25.31 %, 26.63 %, 33.92 %, 7.23 %, 1.497 %; and the average values for IgG, IgA and IgM in BCP were 136.31 mg/g, 27.31 mg/g and 4.22 mg/g respectively. The obtained results also illustrated that these compositions in BCP samples were decreased from 0.87 to 62.67 % compared with those in pasteurized colostrums samples, depending on the nature of each component in the colostrums. For instance, lactoferrin and total protein were lost 43.3 % and 34.76 %; IgG, IgA and IgM were decreased 22.57 %, 15.48 % and 45.41 %; while lactose and minerals were just lost 3.66 % and 0.87 %.